STIMULATING STUDENTS' CREATIVE THINKING IN THE PROCESS OF THEIR EDUCATIONAL ACTIVITIES - Sh. M. Kholmatova; Sh. M. Abduganiyeva (Bright Mind Publishing, 2025)
The modern educational system aims to create conditions that ensure the comprehensive development of individuals capable of independent thinking and creative activity. In the context of a growing demand for creative specialists, the humanization of education and the formation of a creatively thinking personality become particularly important. Creativity is viewed as the ability to generate original, non-standard ideas and to find effective solutions that go beyond traditional thinking patterns. This article examines the essence of creativity, its key characteristics and conditions for development, and highlights the role of innovative educational technologies—problem-based and project-based learning, research and game methods, brainstorming, and creative tasks—in stimulating students’ creative potential. It is concluded that the integration of innovative approaches into the educational process contributes to the development of students’ creative thinking, enabling them to compete successfully in the scientific sphere and labor market.
Keywords: Creativity, creative thinking, innovative technologies, humanization of education, creative potential, students, creative activity, originality, educational process.